2020
DOI: 10.1590/0001-3765202020180837
|View full text |Cite
|
Sign up to set email alerts
|

Fetal lesions of EHV-1 in equine

Abstract: EHV-1 infection is responsible for huge economic losses in equines due to abortion and neonatal mortality. In this study, we describe 4 cases of abortion and neonatal deaths from pregnant mares and a she-donkey from different localities in Egypt during the period from May 2015 to October 2017. Attempts were made to isolate and identify EHV-1, in addition to compare the different pathological lesions in various tissues of the necropsied cases. EHV-1 was successfully isolated from two aborted fetuses and one dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
1
3
1
Order By: Relevance
“…This observation was supported by (Smith et al 2003;Laugier et al 2011) they reviewed that EHV-1 is the most prominent equine viral disease-initiating abortion with sporadic occurrences happened from latent virus reactivation, rather than from new EHV-1 infection. The above-mentioned results agreed with Ali et al (2020) who recorded that clinical signs in one of two sporadic cases of EHV-1 aborted mares included anorexia with mild respiratory manifestation, while the other mare aborted without any detectable clinical signs. Our findings were in partial agreement with Slater (2014) who demonstrated that EHV-1 abortion occurringsuddenly in the last third of pregnancy with the fetus still contained in the allantochorion is suggestive but not diagnostic of EHV-1 abortion.…”
Section: Discussionsupporting
confidence: 90%
“…This observation was supported by (Smith et al 2003;Laugier et al 2011) they reviewed that EHV-1 is the most prominent equine viral disease-initiating abortion with sporadic occurrences happened from latent virus reactivation, rather than from new EHV-1 infection. The above-mentioned results agreed with Ali et al (2020) who recorded that clinical signs in one of two sporadic cases of EHV-1 aborted mares included anorexia with mild respiratory manifestation, while the other mare aborted without any detectable clinical signs. Our findings were in partial agreement with Slater (2014) who demonstrated that EHV-1 abortion occurringsuddenly in the last third of pregnancy with the fetus still contained in the allantochorion is suggestive but not diagnostic of EHV-1 abortion.…”
Section: Discussionsupporting
confidence: 90%
“…Recent years, mare abortion cause enormous economic loss in the donkey industry every year in China. Previous study suggested that EHV-1 and EAV could cause abortion of equine [ 18 , 19 ], however, they are negative in present study. Interestingly, the infection of PCV3 in donkey with reproductive failure was firstly detected in our study.…”
Section: Discussioncontrasting
confidence: 79%
“…These results confirmed that EHVs are still circulating in Egypt’s northern governorates, with significant health impacts and economic losses due to the lack of vaccination programs and frequent virus reactivation, which could threaten the stability of the Egyptian horse industry in agreement with Salib et al (2016 ), Azab et al . (2019 ), and Ali et al (2020 ).…”
Section: Discussionmentioning
confidence: 96%